Valuable nutrients and functional bioactives in different parts of olive (Olea europaea L.)-a review - Ghanbari, Rahele; Anwar, Farooq; Alkharfy, Khalid M.; Gilani, Anwarul Hassan; Saari, Nazamid (MDPI AG, 2012)
The Olive tree (Olea europaea L.), a native of the Mediterranean basin and parts of Asia, is now widely cultivated in many other parts of the world for production of olive oil and table olives. Olive is a rich source of valuable nutrients and bioactives of medicinal and therapeutic interest. Olive fruit contains appreciable concentration, 1–3% of fresh pulp weight, of hydrophilic (phenolic acids, phenolic alchohols, flavonoids and secoiridoids) and lipophilic (cresols) phenolic compounds that are known to possess multiple biological activities such as antioxidant, anticarcinogenic, antiinflammatory, antimicrobial, antihypertensive, antidyslipidemic, cardiotonic, laxative, and antiplatelet. Other important compounds present in olive fruit are pectin, organic acids, and pigments. Virgin olive oil (VOO), extracted mechanically from the fruit, is also very popular for its nutritive and health-promoting potential, especially against cardiovascular disorders due to the presence of high levels of monounsaturates and other valuable minor components such as phenolics, phytosterols, tocopherols, carotenoids, chlorophyll and squalene. The cultivar, area of production, harvest time, and the processing techniques employed are some of the factors shown to influence the composition of olive fruit and olive oil. This review focuses comprehensively on the nutrients and high-value bioactives profile as well as medicinal and functional aspects of different parts of olives and its byproducts. Various factors affecting the composition of this food commodity of medicinal value are also discussed.